Field notes contributed by Hank Zaletel, summer 1996 - Zaletel, Hanket al (1996)
List of birds and locations contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1996. Epson - sheet feed